Rapid expansion of the maxilla and its impact on the upper airway aspect: bibliographic review - Delgado, Camila (2019)
Maxillary expansion, whether rapid or slow, has been a procedure used for years to correct transverse malocclusions. Its benefits and effects at the dental aspect, such as the middle palatal suture are well known. Lately, however, its repercussion and effects at the airway aspect, have been studied and established as a point of interest; especially during the treatment of patients with respiratory problems. According to current bibliography, rapid maxillary expansion is associated with an increase in the upper airway volume. Nowadays, with the high development of techniques based on 3D images and with the inception of Cone Beam computed tomography, it is possible to perform quantitative analysis and evaluate the effects of maxillary expansion on the upper airway in a three dimensional way. With the use of imagenology, it is possible to visualize the increase in the upper airway dimensions, however, there is no evidence that this increase somehow, improves the respiratory function.